MANAJEMEN SUMBER DAYA MANUSIA DI PERPUSTAKAAN SMK NEGERI 1 PONTIANAK - Sari, Rolly Novita; Hanum, Atiqa Nur Latifa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractHuman resource is one of the important parts of organizing a library. However, the human resources at the library of SMKN 1 Pontianak have not been well-organized in carrying out the given tasks. Therefore, human resource management is necessary for making the works are carried out maximally and systematically. Reviewing the implementation of management function on human resources management and difficulties in implementing it, this study aims to determine the implementation of the human resource management function in the library of SMKN 1 Pontianak. This study is descriptive research using the qualitative method. The data were collected through observation, interview, and documentation techniques. Three informants participated in this study. Based on the results, the management function on human resource management has been ineffectively implemented for it was only applied based on needs at the library. In the practice, not all the plans made was able to execute since their capabilities were limited. If the management of human resources is not implemented, it will result in work activities in the library becoming unsystematic because they do not fully understand the system of the school library, the work planning, and the work division that is beyond their capabilities. Keywords: Management, Human Resources, School Library